2019
DOI: 10.1055/s-0039-1692684
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Partially Hydrolyzed Formula on Severity and Outcomes of Neonatal Abstinence Syndrome

Abstract: Objective This article compares the effect of partially hydrolyzed formula (PHF) and standard formula (SF) on the severity and short-term outcomes of neonatal abstinence syndrome (NAS). Study Design We performed a retrospective chart review of 124 opioid-dependent mothers and their term or near-term infants. Infants were categorized according to the predominant type of formula consumed during the hospital stay. Finnegan's scale was used to assess symptoms of withdrawal. Results A total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…In total, 65 cross-sectional and 23 longitudinal studies (81 unique publications), involving 20 indicators and 3 875 183 individuals from 11 different countries met the inclusion criteria ( figure 1 ). Overall, 13 studies provided indicators for NAS, 36–45 7 for FAS, 46–52 50 for CM (0–18 years) 14 53–98 and 18 for IPV among women (12–50 years). 99–116 Most studies were from the USA (72 studies, 81%), with a minority from Australia (8 studies, 9%) and Europe (4 studies, 4%).…”
Section: Resultsmentioning
confidence: 99%
“…In total, 65 cross-sectional and 23 longitudinal studies (81 unique publications), involving 20 indicators and 3 875 183 individuals from 11 different countries met the inclusion criteria ( figure 1 ). Overall, 13 studies provided indicators for NAS, 36–45 7 for FAS, 46–52 50 for CM (0–18 years) 14 53–98 and 18 for IPV among women (12–50 years). 99–116 Most studies were from the USA (72 studies, 81%), with a minority from Australia (8 studies, 9%) and Europe (4 studies, 4%).…”
Section: Resultsmentioning
confidence: 99%
“…One retrospective study by Alsaleem et al compared hydrolyzed versus standard term formula and breast milk and reached similar outcomes to our study. 26 Their study included 34 hydrolyzed infants, 60 term standard formula, and 16 breastfeeding babies. They concluded that partially hydrolyzed formula had no benefit in terms of morphine treatment length, but that they often required increased caloric content to achieve growth parameters.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that partially hydrolyzed formula had no benefit in terms of morphine treatment length, but that they often required increased caloric content to achieve growth parameters. 26 Bogen et al investigate term standard formula versus term formula fortified to 22 calories, and determined that there may be benefit of early return to birthweight not reaching significance and weight gain over time which did reach significance. 8 Bogen et al also examined stooling frequency between the two groups of standard calorie and higher calorie infants and found that they were equivocal.…”
Section: Discussionmentioning
confidence: 99%
“…For this review's specific aim, we focused mainly on whether using LLF was more beneficial regarding short-term outcomes in infants with NAS. Alsaleem et al 11 and Pandey et al 14 reported the type of LLF (Similac Sensitive (Abbott, Columbus, OH), and/or Enfamil Gentlease (Mead Johnson & Co., Glenview, IL)) that was used in the analysis. The other 2 studies did not specifically mention the kind of LLF used in the study population.…”
Section: Study Selectionmentioning
confidence: 99%
“…Among 41 articles selected, 4 met the inclusion criteria: 2 cohort studies, 1 randomized controlled trial, and 1 quality improvement study, Figure 1. [11][12][13][14] The inclusion of 1 other study was ruled out after discussion and agreement between the authors. 15 Study types, methodology, and limitations are shown in Table 1.…”
Section: Study Selectionmentioning
confidence: 99%